The Impact of Household Hazardous Waste upon the Environment Pollution - Sarkees, alaa; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2006)
Objectives: To determine the impact of the household hazardous waste’s aspects upon the environmentpollution .and to identify the relationship between the households’ demographic characteristics and the aspectsof household hazardous waste.Methodology: A descriptive study is conducted between December 14th 2004 to October 20th 2005that uses ofan assessment tool. A probability (simple random sampling) of (336) principal’s households which is selectedfrom the zones around the (14) primary health care centers as focal points, (8) in the urban and (6) in the ruralareas of Baghdad Governorate. After reliability and validity were determined Data are collected through the useof an assessment tool that is consisted of households’ demographic characteristics and factors that producehousehold hazardous waste, awareness towards such waste, and management of this waste.Data is performed through the use of descriptive statistical approach (frequencies and percentages) andinferential statistics (stepwise multiple regression analysis).Results: The findings reveal that the aspect of awareness towards household’s hazardous waste has a greaterimpact upon the household hazardous waste than factors that produce this waste and management of such waste.The study concludes that Low-educated, being in extended family and living with moderately orientedsocioeconomic status have influenced the households’ awareness towards their hazardous waste andidentification of factors that contribute to such waste and their management of this waste.Recommendation: The study recommends that the Public Awareness Programs can be designed, constructedand presented to increase their awareness towards identification of factors that produce such waste and itsmanagement.